Gangs and society : alternative perspectives - Kontos, Louis; Brotherton, David; Barrios, Luis. (New York : Columbia University Press, 2003)
This volume addresses timely questions from an eclectic range of positions and brings together the work of academics, activists, and community leaders to examine the many functions and faces of gangs today. Analyzing the spread of gangs from New York to Texas to the West Coast, the book covers such topics as the spirituality of gangs, the place of women in gang culture, and the effect on gangs of a variety of educational programs and services for at-risk youth.
A note on social theory and the American street gang / Sudhir Venkatesh -- Toward a typology of contemporary Mexican American youth gangs / Avelardo Valdez -- The negligible role of gangs in drug distribution in New York City in the 1990s / Ric Curtis -- Marginal youth, personal identity, and the contemporary gang: reconstructing the social world? / Kevin McDonald -- Gangs and the contemporary urban struggle: an unappreciated aspect of gangs / Albert DiChiara, Russell Chabot -- Urban street activists: gang and community efforts to bring peace and justice to Los Angeles neighborhoods / Juan Francisco Esteva Martinez -- The almighty Latin king and queen nation and the spirituality of resistance: agency, social cohesion, and liberating rituals in the making of a street organization / Luis Barrios -- Education in the reform of street organizations in New York City / David Brotherton -- Liberating yet limiting: the paradox of female gang membership / Dana Nurge -- Amor de reina! The pushes and pulls of group membership among the Latin queens / David Brotherton, Camila Salazar-Atias -- Gangs and the law / Loren Siegel -- The gang crackdown in the prisons of Massachusetts: arbitrary and harsh treatment can only make matters worse / Phillip Kassel -- On the subject of gang photography / Richard Rodriguez -- From civil war to gang war: the tragedy of Edgar Bolanos / Donna DeCesare -- Snapshots of a movement: the New York Latin kings and queens 1996-99 / Steve Hart, David Brotherton.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Gangs -- United States; Gangs -- États-Unis.; FAMILY & RELATIONSHIPS -- Friendship; Gangs; United States